Kajian Konsep Arsitektur Hibrid pada Bangunan Gedung Sarbonne, Pondok Pesantren Tazkia, Malang - Rafly, Ramadhan Fawwaz; Satwikasari, Anggana Fitri (CV. Gio Architect, 2025)
Hybrid architecture represents the integration of two distinct design elements, harmonizing functionality and strength in both form and style. This concept has the potential to enhance building quality based on indicators such as durability, flexibility, energy efficiency, and cost-effectiveness. In the context of higher education, educational buildings not only serve as spaces for learning but also as hubs for interaction, knowledge exchange, and intellectual development. However, the disparity in educational facilities, particularly in underdeveloped, remote, and outermost areas (3T regions), remains a significant challenge in Indonesia. According to data from the Ministry of Education and Culture of Indonesia, approximately 25% of schools are located in isolated regions with limited access. This study aims to explore how the application of hybrid architectural principles in the design of higher education buildings can enhance comfort and foster public interest in educational activities. Additionally, it seeks to demonstrate the advantages of hybrid architecture in creating high-quality designs that provide innovative solutions to address disparities in educational facilities in 3T areas. Through this approach, the research aspires to contribute to equitable education infrastructure across Indonesia.